Did the 2008 global economic crisis affect large firms in Europe? - Raźniak, Piotr; Winiarczyk-Raźniak, Anna (Acta geographica Slovenica, 2015)
The paper analyses the spatial distribution of the largest global corporations found on the Forbes Global 2000 list and with headquarters in Europe. The analysis includes the effects of the 2008 global financial crisis on changes in corporate financial performance. Research has shown that London has the largest economic potential in Europe, while companies in Central and Eastern European cities exhibit high rates of growth. The crisis triggered a decentralisation of corporate headquarters’ location resulting in more cities with corporate headquarters.